Volumetric changes in specific neurofunctional subfields of the hippocampus in major depressive disorder. Issue 9 (11th May 2022) - Wang, Yuning; Wang, Yi; Zhou, Jing; Ge, Chenjin; Shi, Yin; Hu, Zhihai
Abstract : Objective: There is evidence that hippocampal volume is abnormal in patients with major depressive disorder (MDD), but there have been no studies on volumetric changes in different subfields based on functional topography. This was investigated in the present study by comparing hippocampal neurofunctional subfield volumes between MDD patients and healthy control (HC) subjects. Methods: Patients with MDD ( n = 44) and HCs ( n = 27) recruited at Shanghai Traditional Chinese Medicine Integrated Hospital underwent a T1-weighted anatomical MRI scan in the sagittal orientation, and the data were used to calculate hippocampal subfield volumes. Logistic regression was used to evaluate the association between the volumes and risk of MDD. A nomogram for predicting MDD risk based on volume changes in different subfields was developed, and its predictive power was evaluated by calculating the concordance (C)-index. Results: Compared with HCs, MDD patients showed reduced volume in hippocampal neurofunctional subfields, specifically in left (L)1, right (R)1, and R2 (related to emotion) and L2, L3, and R4 (related to cognition and perception). The logistic regression analysis revealed that the risk of MDD was 4.59-, 5.8-, 8.33-, and 6.92-fold higher with atrophies of L1, L2, L3, and R4, respectively. A nomogram for predicting MDD risk was developed based on age; sex; and hippocampal L1, L2, L3, and R4 subfield volumes and showed good accuracy, with a C-index of 0.784. Conclusion: Volumetric changes in the neurofunctional subfield of the hippocampus are potential imaging markers that can predict the occurrence of MDD.